An empirical study of soft real-time performance of windows multimedia timer for mechatronics application / Koh Wei Kiat … [et al.] - Koh, Wei Kiat; Md Saad, Mohd Hanif; Mohd Nor, Mohd Jailani; Ngadiran, Ruzelita (2004)
This paper presented an empirical study of the performance of soft real time multimedia timer in mechatronics application. Most mechatronics systems need periodic functionality and high precision timing capability. Normal operating system timer has low priority and can experience delays, unpredictable timing period and has low timing precision. In this paper, the behavior and characteristic of Windows OS multimedia timer is studied and compared with the normal Windows OS timer. Both timers behavior due to three types of loads were observed and studied. The observation shows that the performance of the Multimedia timer is far superior in terms of predictability and timing precision as compared to normal timer. An application of the multimedia timer in a hardware-in-the-Ioop mechatronics vehicle simulation system is also discussed at the end of this paper.